Arms Lift in a Case of Pseudoxanthoma Elasticum - P. Panettiere; L. Marchetti; D. Accorsi (Case Reports in Dermatological Medicine)
Pseudoxanthoma elasticum (PXE) is a rare hereditary disorder of elastin fibers, characterized by yellowish coalescent papules in flexural surfaces with abnormally lax and corrugated skin. It can be associated to systemic manifestations mostly regarding eyes and vessels. Aesthetic surgery of cutaneous hyperlaxity was described in the international literature only in few cases, mostly as neck lift. A 40-year-old woman presented with cutaneous signs of PXE, demanding brachioplasty. Results after a nine-month followup are quite satisfying, and no signs of local recurrence or scar alterations are present.